ANGGREK PENSIL (Papilionanthe hookerina) ASLI BENGKULU SEBAGAI SPESIES BARU - Roilan Roilan (Jurnal Ilmu Lingkungan, 2016)
Cagar Alam Danau Dendam Tak Sudah already undergone several expansion area. First in 1936, where the Dutch East Indies government designated it a nature reserve with a total area of 11.5 hectares. In 1979, the nature reserve area dipeluas again to 430 hectares. Until 1999, the total area to 577 hectares. This lake is a prime habitat for rare endemic plants, the orchids pencil (Papillionanthe hookeriana). Other species also live here like a sun orchids, palm, plawi, island, daffodils, gelam, stretched, sikeduduk, brosong, acang swamp, and ferns. The beauty of this orchid is able charming British government and society so that in 1882 was named the "Queen of Orchids" and awarded "First Class Certificate". However, in the habitat of the Danau Dendam Tak SudahNot It rare orchid is increasingly difficult to find However, like other endangered species in the country, exploits make drastic shrinking population and since the early 1990s, Orchid Pencil rare start. Conditions that are threatened by extinction it makes BKSDA Bengkulu attempt to do multiplication and release the back to the lake in 2007 and 2008.